ВОПРОС ОБ АНТРОПОЦЕНТРИЧЕСКОМ ЛЕКСИКОГРАФИРОВАНИИ СИНОНИМОВ РУССКОГО СЛОВА В ДВУЯЗЫЧНОМ СЛОВАРЕ - Аттиа, Ашраф М. (Journal of Oriental Studies, 2016)
It is recognized that the synonyms of the Russian language capabilities are great. For the expression of a concept can be used not one word to express the range and variety of shades of meaning. In this case the inability to choose words and designs that express the desired value, leads to a semantic error. Information about the characteristics of synonyms, the difference between them is very relevant to any speaker in that language, rather than an interpreter, who must learn the differences between synonyms for the correct, adequate expression of the concept. In this paper we examine how the Russian synonyms are presented in a Russian-Arabic dictionary and will be presented the mechanism of the lexicographic description of the studied units, which would take into account all aspects of synonyms.